1983
DOI: 10.1055/s-2007-969935
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Plants of Surinam

Abstract: From Aspidosperma excelsum, rootbark, which has previously been shown to exhibit antimicrobial activity, 6 antimicrobial active alkaloids were isolated and identified: il-methoxytubotaiwine, ochrolifuanine A, tetrahydrosecamine, 16-demethoxycarbonyltetrahydrosecamine, 16-hydroxytetrahydrosecamine and 1 6-hydroxy, 16-demethoxycarbonyltetrahydrosecamine. The minimum inhibitory concentration was determined for some of the alkaloids, using Bacillus subtilis as test organism. Didemethoxycarbonyltetrahydrosecamine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0
2

Year Published

1986
1986
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 10 publications
2
15
0
2
Order By: Relevance
“…A característica marcante desse gênero é a presença de alcaloides indólicos, principalmente os monoterpênicos, 3 que conferem um amplo espectro de atividades biológicas reconhecidas às espécies desse gênero, tais como antitumoral, 4 antiplasmódica, 5 antimicrobiana, 6 e antibacteriana 7 consistentes, em muitos casos, com suas utilizações populares. Dentre essas atividades biológicas, a mais representativa é a citotóxica, que tem sido demonstrada frente a diferentes linhagens de células tumorais.…”
Section: Introductionunclassified
“…A característica marcante desse gênero é a presença de alcaloides indólicos, principalmente os monoterpênicos, 3 que conferem um amplo espectro de atividades biológicas reconhecidas às espécies desse gênero, tais como antitumoral, 4 antiplasmódica, 5 antimicrobiana, 6 e antibacteriana 7 consistentes, em muitos casos, com suas utilizações populares. Dentre essas atividades biológicas, a mais representativa é a citotóxica, que tem sido demonstrada frente a diferentes linhagens de células tumorais.…”
Section: Introductionunclassified
“…Além disso, são responsáveis pelos efeitos alucinógenos do tabaco, de bebidas e rapés utilizados por nativos da Amazônia, bem como pelas propriedades sedativas do maracujá 23 . Ensaios biológicos de muitos alcalóides monoterpênicos isolados das cascas de A. quebracho-blanco 22 indicaram atividade bloqueadora α-adrenérgica e ação inibitória de contrações de mús- 36 .…”
Section: Introductionunclassified
“…13,18 The structures of alkaloids 5−8 were established by analysis of 1D and 2D NMR data (COSY, HSQC, HMBC, NOESY) ( Table 2). The similarity of these data indicated that these compounds were closely related.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Alkaloids 4 and 9 are the known compounds O-demethylaspidospermine and the β-carboline alkaloid flavopereirine, respectively. 13,14 The antiparasitic activities of the bark and leaf extracts and pure alkaloids against Trypanosoma cruzi and Leishmania infantum (the etiological agents of Chagas disease and leishmaniasis, respectively) and the cytotoxic effects on mammalian cells (CHO cell line) were tested.…”
mentioning
confidence: 99%